HUBUNGAN RASIONALITAS PENGGUNAAN ANTIBIOTIK DENGAN TINGKAT PENGETAHUAN PADA MASYARAKAT SEMARANG UTARA - Wijianto, Deshinta Putri; Suwarni, Sri; Indrasari, Ferika; Ristita, Cinthya Nisha; Santoso, Arifin (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2022)
Antibiotics have side effects of resistance if not used appropriately and rationally, Antibiotic resistance occurs because antibiotics lack the ability to control or kill microbial growth. Thus, to prevent the occurrence of antibiotic resistance must be taken appropriately. Knowledge in the correct use of antibiotics is an important role in the success of treatment process. The correct level of knowledge about antibiotics will affect the rationality in using antibiotics. The purpose of the study was to determine the relationship between the level of public knowledge on the rationality of antibiotics in North Semarang Community. This research was conducted with survey research method prospective survey research method with the population in this study is the community in North Semarang Subdistrict which amounted to 125,352 people, a sample of 405 was taken by purposive random sampling, by purposive random sampling. The data obtained were analyzed using the Spearman correlation test statistical test. Results of community knowledge level in North Semarang Sub-district North Semarang Subdistrict as a whole was categorized as “moderate” as many as 191 respondents (47.2%). respondents (47.2%). People in North Semarang Sub-district as a whole used antibiotics rationally as many as 211 respondents (52.1%). The level of knowledge influenced the rational use of antibiotics in North Semarang District (0.000 < 0.050) there is a significant correlation between the two variables. variables that are connected. The correlation coefficient value is 0.614 the strength of the correlation obtained is included in the strong category. There is a relationship between knowledge level on the rationality of antibiotic use in the community of North Semarang District.